A proteomic analysis shows the stimulation of light reactions and inhibition of the Calvin cycle in the skin chloroplasts of ripe red grape berries - Teixeira, António; Noronha, Henrique; Sebastiana, Mónica; Fortes, Ana Margarida; Gerós, Hernâni (Frontiers in Plant Science, 2022)
The role of photosynthesis in fruits is still challenging scientists. This is especially true in mature grape berries of red varieties lined by an anthocyanin enriched exocarp (skin) almost impermeable to gases. While in several fruits chlorophylls are degraded and replaced by carotenoids, available evidence suggests that they may persist in red grapes at maturity. In the present study, chloroplasts were isolated from the skin of red grape berries (cv. Vinhão) to measure chlorophylls and the organelle proteome. Results showed that chloroplasts (and chlorophylls) are maintained in ripe berries masked by anthocyanin accumulation, and that the proteome of chloroplasts from green and mature berries are distinct. Several proteins of the light reactions were significantly accumulated in chloroplasts at the mature stage, including from photosystems II and I light harvesting complexes, redox chain, and ATP synthase, while chloroplasts at the green stage accumulate more proteins involved in the Calvin cycle and in the biosynthesis of amino acids, including precursors of secondary metabolism. Taken together, results suggest that while in green berries chloroplasts are more involved in biosynthetic reactions, in mature berries they may provide ATP and reducing power for cell metabolism or even O2 to feed the respiratory demand of inner tissues.